Drug Delivery and Magnetic Hyperthermia Based on Surface Engineering of Magnetic Nanoparticles - Lucena, Guilherme N. [UNESP]; dos Santos, Caio C. [UNESP]; Pinto, Gabriel C. [UNESP]; Amantéa, Bruno E. [UNESP]; Piazza, Rodolfo D. [UNESP]; Jafelicci, Miguel [UNESP]; Marques, Rodrigo Fernando C. [UNESP] (Wiley, 2021)
Magnetic nanoparticles (MNP) have highlighted its relevance in biomedical applications as drug delivery and magnetic hyperthermia devices due to their high surface area, low toxicity, and biocompatibility, as well as intrinsic magnetic properties. In addition, a fine surface engineering of MNP can be used as an approach for a careful adjustment of its target cell recognition capacity and improvement of its intrinsic properties with other biomedical relevance, such as colloidal stability. Thus, this chapter focuses on the exploitation of different MNP surface engineering strategies for the enhancement of therapies based on drug delivery and magnetic hyperthermia. It is reported that MNP surface can be tuned to further modifications, e.g. with biomarkers and how such a surface engineering can improve important properties for its biomedical applications, such as biocompatibility, cell recognition, magnetic properties, and colloidal stability.
Keywords: biomarkersbiomedical applications; magnetic nanoparticles; surface modification